2012
DOI: 10.1111/j.1447-0594.2012.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

More than half of hip fracture patients do not regain mobility in the first postoperative year

Abstract: The risk not to regain prefracture mobility is highest in mobile patients without an aid. The risk of becoming immobile is higher in those having a lower prefracture mobility. Activities of daily living dependence and delirium were the main risk factors for not regaining mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 20 publications
7
77
2
3
Order By: Relevance
“…Between 40 and 60 % of hip fracture survivors are likely to recover their prefracture level of mobility [25,37,47]. Up to 70 % of people may regain their pre-fracture level of independence for composite measures of basic ADL [22,48,51], but this proportion is likely to be lower for those with higher levels of dependence pre-fracture [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 40 and 60 % of hip fracture survivors are likely to recover their prefracture level of mobility [25,37,47]. Up to 70 % of people may regain their pre-fracture level of independence for composite measures of basic ADL [22,48,51], but this proportion is likely to be lower for those with higher levels of dependence pre-fracture [48].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have indicated that the proportion recovering their pre-fracture mobility can continue to increase beyond 3 months (Table 4) [37,44]. However as these data represent mobility in survivors, this may indicate longer survival of those with better mobility.…”
Section: Activity Outcomes Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This compares with less than half of treated patients who regained their pre-fracture mobility in another study. 15 According to an internal survey conducted at Prince of Wales Hospital, only 22% of patients received out-patient physiotherapy; the major reason (71%) was "not referred". Inadequate rehabilitation after discharge may explain poor functional recovery after Poor functional recovery after hip fracture may contribute to this high institutionalisation rate, as fractures are significantly associated with mildto-severe functional limitations.…”
Section: Consequences Of Fragility Hip Fracturementioning
confidence: 99%
“…Sechs Monate nach einem Sturzereignis beträgt die Mortalität zwischen 11-23 %, nach einem Jahr zwischen 22-29 % und nach fünf Jahren bis zu 47 % (Haleem, Lutchman, Mayahi, Grice, & Parker, 2008). Zudem erreichen 50 % der Gestürzten nicht mehr dasselbe Mobilitätsniveau wie vor der Fraktur (Vochteloo et al, 2013). Die Frakturfolgen gehen darüber hinaus auch mit einer erheblichen Verminderung der Autonomie und damit der Lebensqualität einher (Rubenstein, 2006).…”
Section: Einleitung Zum Format Der Potenzialanalyseunclassified